2022
DOI: 10.1021/acsaelm.2c00824
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Wet-Etch Directionality in Nanostructured Silicon

Abstract: Anisotropic wet etching of crystalline silicon (c-Si) is a key chemical process used in microelectronic device fabrication. Controlled fabrication of c-Si nanostructures requires an understanding of how crystal planes evolve during silicon etching. Here, by imaging KOH wet etching of c-Si nanowires, we show that it is possible to switch the fast-etching direction (i.e., the etch anisotropy) between the Si {100} and {110} crystal planes at will through mechanical agitation of the etchant. Based on molecular dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…To better understand how the NW surface evolves during the etching, we tracked the entire process in real-time with LP-TEM (Figure 3). [25,[28][29][30] The plot of the width of Mo NWs (Figure 3B) extracted from the in situ TEM images series (Figure 3C; Video S1, Supporting Information) shows the gradual width recess for four metal NWs, where the etching rate, defined as the rate of the NW width reduction, remained almost constant at ≈0.02 nm s −1 throughout the etching. However, a closer examination of the selected area in Figure 3D reveals that some pits formed at the GBs at the early stage (Figure 3D: t -t 0 = 0-130 s), suggesting that GBs are more susceptible to etching than the sidewalls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To better understand how the NW surface evolves during the etching, we tracked the entire process in real-time with LP-TEM (Figure 3). [25,[28][29][30] The plot of the width of Mo NWs (Figure 3B) extracted from the in situ TEM images series (Figure 3C; Video S1, Supporting Information) shows the gradual width recess for four metal NWs, where the etching rate, defined as the rate of the NW width reduction, remained almost constant at ≈0.02 nm s −1 throughout the etching. However, a closer examination of the selected area in Figure 3D reveals that some pits formed at the GBs at the early stage (Figure 3D: t -t 0 = 0-130 s), suggesting that GBs are more susceptible to etching than the sidewalls.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the fabrication steps of the chips and liquid cells are described in our earlier studies. [25,[28][29][30] Materials: The etching solutions used in this study were prepared from the following chemicals: hydrogen peroxide (30% H 2 O 2 , Dickson Chemical, Singapore), hydrofluoric acid (48% HF, Cat. No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, precipitation phenomena observed in aqueous solutions and analyses of growth kinetics suggest an elevated concentration of c (OH – ) under irradiation. Likewise, LP-TEM studies on c (OH – )-driven Si etching are reported. , This is unexpected at low pH.…”
mentioning
confidence: 76%
“…Likewise, LP-TEM studies on c(OH − )-driven Si etching are reported. 19,20 This is unexpected at low pH.…”
mentioning
confidence: 91%